Analisis Strategi Pengembangan Usaha Home Industri Keripik Pisang di Kota Unaaha - Endang Sumiratin (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2026)
The purpose of this study is to analyze the development strategy of a banana chip business as an effort to make this business a resilient and competitive business, thus adding value to the surrounding environment and to the banana chip entrepreneurs. The data collection techniques used for the banana chip business development strategy include primary and secondary data, including interviews, questionnaires, and data processing. The first stage involves inputting data to determine the IFAS and EFAS values, followed by using a SWOT matrix to identify alternative strategies. Based on the research results, the banana chip business has five strengths, five weaknesses, five opportunities, and four threats. The strategy for developing the banana chip business is in quadrant I, indicating that the banana chip business faces an environment with a relatively greater opportunity to overcome its weaknesses, specifically the Strengths-Opportunities (SO) strategy. This position indicates that there are opportunities for business development and a strong position for growth.